1994
DOI: 10.1007/bf00808118
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and biological activity ofβ-thymosins

Abstract: β-Thymosins, a group of highly homologous peptides consisting of about 40 amino acid residues, were found to be distributed from mammals up to echinoderms. Althogh they have first been isolated from mammalian thymus tissue preparations, their occurrance is not organ-specific and they are present even in different types of cells. For thymosinβ 4 several biological activities have been reported, stating that this peptide acts as a thymus peptide hormone and is also involved in the neuroendocrine and immune syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 72 publications
0
8
0
1
Order By: Relevance
“…It seems to be controversial with previous study in which high expression of thymosins were found in mammalian thymus (Haritos et al, 1984). Although thymosins were firstly isolated from mammalian thymus tissue preparations, their occurrences were not tissue-specific and they were even present in different types of cells (Mihelic and Voelter, 1994). These studies suggested that multiple roles of thymosins may exist in teleosts and mammals, which needs further investigation.…”
Section: Discussionmentioning
confidence: 87%
“…It seems to be controversial with previous study in which high expression of thymosins were found in mammalian thymus (Haritos et al, 1984). Although thymosins were firstly isolated from mammalian thymus tissue preparations, their occurrences were not tissue-specific and they were even present in different types of cells (Mihelic and Voelter, 1994). These studies suggested that multiple roles of thymosins may exist in teleosts and mammals, which needs further investigation.…”
Section: Discussionmentioning
confidence: 87%
“…Later on Safer et al [9] isolated a G‐actin sequestering factor, Fx, and showed that this factor is identical to thymosin β 4 [10]. The query that nearly all mammalian tissues investigated up to now express two members of this family has not been clarified [11, 12]. Most recently a third β‐thymosin (β 15 ) has been detected in Dunning rat prostate carcinoma additionally to thymosin β 4 and β 10 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Tβ4 is a 43 amino acid, 4.9 kDa ubiquitous polypeptide found at concentrations of 1 ϫ 10 -5 to 5.6 ϫ 10 -1 M in a variety of tissues and cell types and was originally isolated from bovine thymus (Weber et al, 1992;Pantaloni and Carlier, 1993;Mihelic and Voelter, 1994;Oates and Goldstein, 1995). Tβ4 can interact with G-actin and is a major actin sequestering protein in cells (Cassimeris et al, 1992;Sanders et al, 1992;Yu et al, 1993Yu et al, , 1994Safer and Nachmias, 1994;Sanger et al, 1995).…”
mentioning
confidence: 98%